Slipping Through the Gap: Exploring the Influence of Social Health Insurance on Access to Healthcare for Older Migrant Workers - Chengxu Long; Wei Yang; Shangfeng Tang (International Journal of Public Health, 2024)
Objectives: Older migrant workers (OMWs) frequently confront barriers to accessing care, as their Social Health Insurance (SHI) coverage may not extend beyond their hometown. This study seeks to investigate whether Chinese OMWs can still derive benefits from SHI in accessing healthcare services, even when their SHI is not registered in the same location as their current residence.Methods: This study used data from 2015 China Migrants Dynamic Survey and focused on OMWs aged 60 years and older (N = 3,050). Logistic regression models were employed to investigate the factors influencing healthcare use.Results: Having SHI registered in current place of residence and interprovincial migration were significantly associated with increased likelihoods of doctor visits among OMWs. However, inpatient services use did not appear to be associated with the SHI registration place and migration range.Conclusion: Chinese OMWs derive fewer benefits from SHI in accessing healthcare services when their SHI is not registered in current residence. Governments in Low- and Middle-Income Countries should consider implementing targeted policies to provide adequate protection for OMWs and expand the coverage of direct reimbursement for cross-province healthcare services.